Photosynthetic acclamatory response of Panicum antidotale Retz. populations to root zone desiccation stress - Javed,M. (2024)
Abstract Growth of plants is severely reduced due to water stress by affecting photosynthesis including photosystem II (PSII) activity and electron transport. This study emphasised on comparative and priority targeted changes in PSII activity due to progressive drought in seven populations of Panicum antidotale (P. antidotale) collected from Cholistan Desert and non-Cholistan regions. Tillers of equal growth of seven populations of P. antidotale grown in plastic pots filled with soil were subjected progressive drought by withholding water irrigation for three weeks. Progressive drought reduced the soil moisture content, leaf relative water content, photosynthetic pigments and fresh and dry biomass of shoots in all seven populations. Populations from Dingarh Fort, Dingarh Grassland and Haiderwali had higher growth than those of other populations. Cholistani populations especially in Dingarh Grassland and Haiderwali had greater ability of osmotic adjustment as reflected by osmotic potential and greater accumulation of total soluble proteins. Maximum H2O2 under water stress was observed in populations from Muzaffargarh and Khanewal but these were intermediate in MDA content. Under water stress, populations from Muzaffargarh and Dingarh Fort had greater K+ accumulation in their leaves. During progressive drought, non-Cholistani populations showed complete leaf rolling after 23 days of drought, and these populations could not withstand with more water stress condition while Cholistani populations tolerated more water stress condition for 31 days. Moreover, progressive drought caused PSII damages after 19 days and it became severe after 23 days in non-Cholistani populations of P. antidotale than in Cholistani populations.